Attempting arts integration: secondary teachers' experiences with spoken word poetry. (3rd April 2018) - Williams, Wendy R.
ABSTRACT: Spoken word poetry is an art form that involves poetry writing and performance. Past research on spoken word has described the benefits for poets and looked at its use in pre-service teacher education; however, research is needed to understand how to assist in-service teachers in using this art form. During the 2016–2017 school year, 15 teachers joined a study group to gather strategies for teaching spoken word. Participants were invited to attend two 4-hour workshops and two public events at a university, and they received monthly bulletins. The year-long qualitative case study included observations, questionnaires, interviews, and artifacts. Materials were analyzed using grounded theory. This study found that teachers had a range of experiences integrating this art form into their classrooms. Some teachers reported meaningful and empowering experiences as they and their students wrote and performed spoken word. Others faced obstacles, including set curriculum and testing, which prevented them from using spoken word at all. Their testimonies reveal varying degrees of teacher agency in regard to curriculum. Teacher education can address these issues by helping teachers anticipate obstacles to integrating new material and by showing teachers how to respond as creative problem-solvers with agency.